RESEÑA de : Estepa Díez, Carlo; Álvarez Borge, Ignacio; Santamarta Luengos, José María. Poder real y sociedad : Estudios sobre el reinado de Alfonso VIII (1158-1214). León : Universidad de León, 2011 - Rodríguez García, José Manuel (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2012)
-